Pengaruh Rasio Keuangan Terhadap Kebijakan Dividen Dan Pertumbuhan Laba Sebagai Variabel Mediasi - Nurul Izza, Aninda Rahma; Suwandi (Journal of Culture Accounting and Auditing, 2025)
This study aims to analyze the effect of financial ratios, namely Net Profit Margin (NPM) and Current Ratio (CR), on dividend policy, with earnings growth as a mediating variable. This research employs a quantitative approach. The research population consists of 12 manufacturing companies in the industrial sector listed on the Indonesia Stock Exchange (IDX). The sampling method used in this study is purposive sampling, in which samples are selected based on predetermined criteria, resulting in 48 observations. The analytical method applied is multiple linear regression analysis using the SmartPLS application. Mediation analysis indicates that dividend policy functions as a significant mediating variable. The effect of the Current Ratio (CR) on earnings growth decreases to -0.15 when dividend policy is included as a mediating variable.